LEGAL PROTECTION OF CONSUMERS DUE TO DEFAULT BY @SELLYALBOEM IN PURCHASING NEO CULTURE TECHNOLOGY (NCT DREAM) ALBUMS - Hikmawati, Cahya Agustianing Durrah; Yasa, I Wayan; Zulaika, Emi (Sekolah Tinggi Ilmu Hukum Awang Long, 2024)
The impact of the internet as a result of advances in the development of information technology for consumers has changed consumer behavior to become more critical and selective in determining the products they will choose. A valid agreement will have an achievement. As is known that an agreement is a relationship between two parties, based on which one party is entitled to demand something from the other party, and the other party is obliged to fulfill these demands. In this case, the achievement can be in the form of giving something, doing something, or not doing something. Although an agreement is made with the hope that everything that has been agreed upon can go well, in practice there is often a non-fulfillment of achievement from one of the parties which gives rise to a situation called default. The problem in this thesis is about the form of legal protection for consumers due to default on the purchase of NCT Dream Albums and dispute resolution efforts that can be taken if there is a default on the purchase of NCT Dream Albums. The research method in this thesis consists of a normative juridical research type with a research approach using a statutory approach and a conceptual approach. The source of legal material uses primary legal materials and secondary legal materials. The results of this study indicate that legal protection for consumers due to default by @Sellyalboem in purchasing Neo Culture Technology (NCT Dream) Albums is divided into two. First, internal legal protection is created through an agreement made by each party. The authorities create second, external protection through the formation of laws and regulations aimed at the interests of the injured party. Business actors who make defaults must make compensation. If they do not make compensation, consumers can be able to make settlement efforts using 2 ways, namely, out-of-court dispute resolution (non-litigation path) and dispute resolution in court (litigation path).